PENGARUH DISIPLIN KERJA DAN KEPEMIMPINAN TERHADAP EFEKTIFITAS KERJA PEGAWAI DI KANTOR DINAS PENDIDIKAN KABUPATEN NIAS BARAT - Iva Mega Sastra Waruwu (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
The aim of this research is to determine the influence of work discipline and leadership on employee work effectiveness at the West Nias Regency Education Office. The type of research used is quantitative research. The data source is from employees, with a population of 33 people and a sample of 33 people. The data collection technique is by distributing questionnaires to respondents, namely employees of the West Nias Regency Education Office. The analytical method used is multiple linear regression analysis. The results of this research show that Work Discipline (X₁) has a significant influence on Work Effectiveness (Y) where the Work Discipline variable (X₁) obtained a value of tcount (2.353)>ttable (1.697) and a significant level of 0.000>0.05. Furthermore, the Leadership variable (X₂) has a significant effect on Work Effectiveness (Y), where tcount (4.598)>ttable (1.697) is obtained with a significance level of 0.000>0.05, which means that partially the Leadership variable (X₂) has a significant effect on the Effectiveness variable. Work (Y). The results of the simultaneous test (F Test), show that the value of Fcount (15.256)>Ftable (3.32) and the significance level is 0.000>0.05, so it can be stated that the variables Work Discipline (X₁) and Leadership (X₂) simultaneously have an effect positive and significant for the Work Effectiveness variable (Y). The coefficient of determination (R²) is 0.504, so it can be interpreted that Work Discipline and Leadership are only able to explain the Work Effectiveness variable by 50.4% while the remaining 49.6% is explained by other variables not mentioned in the research.